The Effect of Servant Leadership on Promoting Employees’ Psychological Resilience: An applied study at Al-Rifa’i Municipal Directorate - Jaber Fzaea, Amal (Iraqi Journal for Administrative Sciences, 2026)
The study aimed to investigate the relationship between servant leadership and psychological resilience among employees at Al-Rifaie Municipality in Thi-Qar, using a quantitative descriptive approach with a sample of 256 employees. The results indicated a strong positive effect of servant leadership dimensions (emotional healing, creating value for the community, empowerment, assisting subordinates in growth and success, putting subordinates first, ethical behavior, and conceptual skills) on psychological resilience dimensions (emotional regulation, cognitive flexibility, social support, sense of meaning and purpose, and self-control and personal efficacy), with varying strengths of influence. It is concluded that servant leadership enhances psychological resilience by fostering a supportive work environment based on trust, capacity building, and a sense of meaning and competence, enabling employees to adapt positively to workplace stressors and professional changes.